Manajemen Strategis Lembaga Pendidikan Islam dalam Meningkatkan Daya Saing dan Keberlanjutan: Studi Kasus Pondok Pesantren Nurul Ittihady Tangerang - Novia Ramadani; Eko Trianto; Nurul Azizah Fitriah; Niki Aulia Putri; Rahmat Aprilia (JMiE (Journal of Management in Education), 2025)
This study analyzes the implementation of strategic management in enhancing the competitiveness and sustainability of Pondok Pesantren Nurul Ittihady Tangerang, which adopts a zero tuition fee education model. Using a qualitative case study approach, data were collected through in-depth interviews, participant observation, and document analysis. The analysis employed SWOT, PESTEL, and Porter’s Five Forces frameworks to examine the institution’s strategic positioning. The findings reveal that the pesantren applies a social cost leadership strategy combined with curriculum differentiation integrating Islamic values, foreign language mastery (Arabic, English, and Mandarin), and digital entrepreneurship. Institutional sustainability is supported by targeted digital marketing, volunteer educators, and funding from leadership-owned business units and community donations. However, financial vulnerability remains due to dependence on personal funding sources, limited financial formalization, and land tenure risks. This study recommends strengthening financial governance, diversifying funding sources, and pursuing permanent asset acquisition to ensure long-term sustainability. The findings offer strategic insights for urban Islamic boarding schools seeking to balance affordable education with institutional resilience.